STUDI PERBANDINGAN REGULATOR KONVENSIONALDUA RELAY DAN REGULATOR ELEKTRONIKBERBASIS MIKROKONTROLERAVR ATMEGA8 - Erma Wijayanti; Gatut Rubiono; Haris Mujianto (ROTOR, 2015)
Automotive charging system provide vehicle’s electricity consumption and battery charging. Common regulator has unstable voltage output. This research is aimed to compare the performance of common and electronic regulator. Electronic regulator designed with an AVR ATMega8 microcontroller and 16 x 2 matrix LCD. The devices are tested in the charging system of Toyota Kijang 5K automotive engine by measuring alternator voltage output using voltmeter. The engine is running at 1000, 1500, 2000, 2500 and 3000 rpm. The measurements are taken three times for 300 seconds with 30 second interval. The result shows that the average voltage output of electronic regulator increase faster at 0 until 30 second measurement period. The result also shows that electronic regulator has more stable voltage output which is 14,45 Volt. The overall comparison study shows that electronic regulator has better performance than common regulator.